Difference Analysis of Digital Marketing Implementation in Enterprises Performance: Balanced Scorecard Perspective - Slamet, Slamet; Adhim, Muhammad Maslukil; Azmala, Ilya (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2021)
This study aims to measure the differences Micro, Small, and Medium Enterprises (MSMEs) performance before and after implementation digital marketing. The research paradigm is a quantitative with primary data sources. The research instrument was a questionnaire designed to measure MSMEs' performance in the balanced scorecard perspective on customer and internal business processes. The number of samples was 107 respondents. Data were collected directly from MSMEs in Malang City. Determination of respondents using judgment sampling approach. Data analysis used descriptive analysis (categorization index) and hypothesis testing (sample paired t-test). The study results show that before and after implementing digital marketing, there are differences in the performance of MSMEs. This difference is evidenced by the results of data analysis, both descriptively and hypothesis testing.